Effect of Some Bio Variables on Gestational Diabetes Progression: (Review) - Alzahraa Ibrahim Abdul Majeed; Ekhlas Abdallah Hassan; Wijdan Amer Ibrahim; Wafaa Sh. Al – Zuhairi (ASJ - Academic Science Journal, 2023)
Gestational diabetes mellitus (GDM) is the most common metabolic disorder and is also defined as: impairment of glucose tolerance. This article aims to clarify the role of the changes in some hormones that may cause the development gestational of diabetes, as an attempt to understand and reduce the mechanism of this disorder. Disturbance Hormonal insulin levels, which are characterized by a reducing blood glucose reduced utilization of by muscle and body tissues. Many factors will promote the development of GDM, such as: BMI ≥ 30 Kg/m2, pre-existing gestational diabetes, family history and HbA1C ≤ 7 mmol/l. Gestational diabetes can be seen as a transient pattern of type 2 Diabetes, Symptoms appear with hormonal changes related to pregnancy. Etiology of GDM related to type 2 diabetes and insulin resistant which also may attack beta cells in pancreas. It can be concluded that the change in the level of each of these hormones (significant differences) had a role in promoting the development of diabetic pregnant more than control pregnant women.